Aging of asphalt binder in hot pavement rehabilitation. (30th October 2018) - Flores, Guillermo; Gallego, Juan; Giuliani, Felice; Autelitano, Federico
Graphical abstract: Highlights: Two heating methods for asphalt pavements were compared: infrared and microwaves. The efficiency of microwaves is higher than that of infrared radiation. Thermographic analysis revealed a more homogeneous heating of asphalt mixtures with microwaves. The aging effect of microwaves on asphalt binder was less significant than the infrared one. Abstract: Construction of new asphalt road pavements as well as traditional maintenance requires the use of a great amount of non-renewable resources, having important negative environmental and economic impacts. Thus, extending the service life and promoting the recycling or reuse of pavement materials represent two pillars of a sustainable development model. These strategies include also two approaches which involve heating and softening of the existing hot-mix asphalt (HMA) pavement, such as healing and hot-in place recycling. Modern and more efficient technologies potentially used for the on-site heating of flexible pavements are no longer based on electrical resistance systems but use microwaves or infrared radiant heaters, which can however lead to a further potential aging of asphalt binder and therefore negatively affecting the mechanical properties of recycled HMA. This article aims, through an experimental laboratory approach, to directly compare two heating methods potentially used in flexible pavement rehabilitation, i.e. infrared and microwave radiations, for a preliminary assessment of the heating process characteristics (temperature distribution, energy consumption and duration) and on asphalt binder aging phenomenon. The thermographic and rheological analyses revealed that microwave radiation represents a more energy-efficient solution compared to infrared, producing minor aging effects on asphalt binder.